A Theoretical Investigation of Surface‐enhanced Sum‐frequency Generation. Issue 1 (5th June 2015) - Yeh, Y. L.; Lei, J.; Chen, S. Y.; Chang, A. H. H.; Lin, C. K.; He, R. X.; Lin, S. H.
Abstract: Following the surface enhanced Raman scattering (SERS), we shall investigate the possibility of observing surface‐enhanced sum‐frequency generation (SESFG), which refers to the transformation of ordinary vibrational SFG (i.e. singly resonant) into SESFG. Two mechanisms of SESFG will be studied; one is due to the transformation of singly‐resonant vibrational SFG into doubly resonant vibrational SFG (that is, both vibrationally resonant and Raman‐scattering resonant) and the other is due to the enhancement of the polarizability in addition to the original vibrational resonance in vibrational SFG. Abstract : This paper presents the theoretical treatments for two types of surface‐enhanced SFG with numerical demonstrations. We investigate the possibility of observing surface‐enhanced sum‐frequency generation (SESFG), which refers to the transformation of ordinary vibrational SFG (i.e. singly resonant) into SESFG. Two mechanisms of SESFG will be studied; one is due to the transformation of singly‐resonant vibrational SFG into doubly resonant vibrational SFG (that is, both vibrationally resonant and Raman‐scattering resonant) and the other is due to the enhancement of the polarizability in addition to the original vibrational resonance in vibrational SFG.